Babuinare - Joana Antunes (Medievalista)
Commonly known for their prolix and heterodox nature, the margins of medieval art present us with a vast array of figures, themes, and representational strategies that deserve to be questioned and learned about. Created to fill voids, to dynamise surfaces and spatial relations, to comment on and amplify the effects anticipated for the centre, they were also invested with playful, prophylactic, and apotropaic functions, so important in medieval culture but still so little studied (and so difficult to study) in Portugal. Among the various protagonists of these margins of medieval art, and particularly from the 13th century on, apes stand out as a satirical and moralising simile of mankind, and, therefore, as the main actors of a topsy-turvy world that finds their natural place in the margins. Attesting to this close relationship, the first known medieval designation for what we now call marginalia, comes from the term babewyn, or baboon, summoning the generality of the simian species and behaviours then known. Based on this affinity, we will seek to identify and, whenever possible, interpret some of the most significant representations of monkeys in medieval marginalia in Portugal during the 14th century, of which two unpublished case studies stand out.